Resolution of Symposium on scientific medical communication «The issue of GERD with discussion of potential of GerdQ questionnaire as additional tool for GERD diagnostics in clinician’s practice» of 26 June 2013 - article Editorial (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
.